Ankyloglossia in the Gambia; A Cause for Concern? - Okoje, Victoria Nwebuni; Sey, Demba; Akinyamoju, Akindayo Olufunto; Omeje, Kelvin Uchenna; Adegbulugbe, Cyril (British Journal of Healthcare and Medical Research, 2026)
Background: Ankyloglossia (AG) is the presence of a short lingual frenum that interferes with normal tongue movement. Prevalence has been estimated to be from less than 1% to 10%. This significant wide range can be attributable to the lack of diagnostic criteria for AG. It is believed that there has been no published study done on the prevalence of Ankyloglossia in the EFSTH or in the Gambia which anecdotical appears to be unusually common and this has informed this prospective study. Objective: To determine the prevalence of tongue tie amongst patients attending the oral and maxillofacial clinics in Edward Francis Small Teaching Hospital (EFSTH) from January 2018 to January 2019. Methods: This is a retrospective descriptive study which was conducted at the oral and maxillofacial clinic of EFSTH from January 2018 to January 2019. The inclusion criterion is all the patients who presented with Ankyloglossia at the oral and maxillofacial clinic and exclusion criteria include those with incomplete records. Results: The study revealed that a total of 44 children with ankyloglossia were seen within the period of study. Which is 10.1% of all the patients seen at the oral and maxillofacial surgery clinic within the study period. 66% of the patients were males. Children between 0-12 months of age accounting for 50%, 13-36 months of age were 25%, while those of ≥109 months accounted for 11.4%, followed by 37-72 months and 73-108 months each accounting to 6.8% respectfully. The study also revealed that majority of those with AG was residing in Kanifing municipal counsel and Brikama area counsel accounting 48% and 45% respectively. The others were residing in Banjul municipal counsel and other areas accounting 6% and 2% respectively. The study has shown that most of those with Ankyloglossia were born by parents of younger age group, ranging 25-35 years. Our study also shows that only 2% of those with ankyloglossia presented with other associated birth defects while 89% presented with difficulty in breastfeeding. Conclusion: Tongue-tie affects a considerable number of infants and children in the Gambia. However, it is important that accurate information and guidance is given to parents with regard to the indications and potential benefits of awareness of the presence tongue-tie and the need for early surgical treatment to prevent malnutrition and possible speech defect.